Park design and children's active play: a microscale spatial analysis of intensity of play in Olmsted's Delaware Park. (November 2015) - Baek, Solhyon; Raja, Samina; Park, Jiyoung; Epstein, Leonard H; Yin, Li; Roemmich, James N
This paper offers a microscale exploration of the role of park design on the intensity of physical activity among youth. The actual, unstructured use of a park—specifically, Delaware Park, an Olmsted-designed park in Buffalo, New York—by ninety-four children was observed and analyzed objectively using geographic information systems, global positioning systems, and accelerometers. Data were analyzed at the scale of 25 ft x 25 ft cells overlaid as a grid on the entire park. Results from the regression analysis show that particular features of parks—especially complexity in landscape surfaces, proximity to sport facilities and playgrounds, and the availability of pedestrian trails—enable greater intensity of youth physical activity in a park.